The Dynamics of Circulating Immune Complexes in Horses with Severe Equine Asthma - Malwina Slowikowska; Joanna Bajzert; Julia Miller; Tadeusz Stefaniak; Artur Niedzwiedz (Animals, 2021)
Non-invasive diagnostic biomarkers of equine asthma syndrome (EAS) from blood or urine are sought. The aim of this study was to assess the absorbance of circulating immune complexes (CICs) during the exacerbation, remission, and treatment of an asthma episode and assess the potential usefulness of CIC levels in the diagnosis and monitoring of the disease. The control group, asthma group, and treated asthma group each contained six horses. Following an initial examination and group classification, the horses were kept in a dusty environment for seven days and then moved to an asthma-friendly environment for three weeks (the treated group received injections of glucocorticoids). Blood was collected at baseline and on the 1st, 2nd, 3rd, 7th, 14th and 30th days. CIC was measured using the modified Haskova method. The time points did not show significant statistical differences. There was a significant decrease in CIC in the treated group, and a significant increase in CIC in the non-treated group on day 30. CIC did not support the EAS diagnosis, although it may help in monitoring patients. To the best of the authors’ knowledge, this is the first study to analyse the dynamics of CIC during environmental challenge, remission, and treatment.